Pengaruh Kombinasi Pemangkasan Ujung Magnet Permanen dan Axial Channel pada inti rotor terhadap Torka Cogging pada Generator Tipe Fractional Slot Number - Suherman, Yudha; Nur, Tajuddin (Jurnal Elektro, 2020)
This paper is about to discuss the effect of combining a magnetic shaping technique with an axial channel in the rotor core to reduce the cogging torque of a permanent magnet synchronous generator. Computation process is performed by using the optimization response surface method. In this case, this research is done by employing two types of axial channel systems, namely circular and hexagonal. The axial channel area at the core of the engine rotor is 0.000279683 m2. Determination of magnetic shaping was carried out with an angle of 10 and a surface angle of 530. The effect of the combination of the cogging torque reduction technique with magnetic shaping and axal channel was analyzed by numerical method based on the finite element method (FEMM). Based on the analysis, it is found that the combination shows a decrease in cogging torque by 98% when compared with the cogging torque in the initial design (initial structure). Another advantage of the combination of the two cogging torque reduction techniques is that there is no significant increase in the magnetic flux density of the engine core. It can be said that the combination of the cogging torque reduction technique and the axial channel at the core of the engine rotor can significantly reduce the cogging torque.